The effectiveness of a training program for conceptual understanding in mathematics on the teaching practices of female teachers in Al-Aidabi Governorate (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to test the effectiveness of the training program in developing conceptual comprehension in mathematics on the teaching practices of female teachers. The study used the quasi-experimental approach with one group. The study sample consisted of (30) female teachers. The results of the study showed that there are statistically significant differences at a significance level of (0.05) in the test of developing conceptual comprehension in mathematics on the teaching practices of female teachers between the pre- and post-application in favor of the post-application. There are no statistically significant differences at a significance level of (0.05) in the test of developing conceptual comprehension in mathematics on the teaching practices of female teachers between the post- and follow-up application. The study recommended the necessity of identifying the training needs of female mathematics teachers to develop their teaching practice in light of the twenty-first century skills.
Keywords: Effectiveness; Training Program; Conceptual Comprehension; Teaching Practices; Female Teachers